Ensuring the strategic focus of a corporate project management system for commercial real estate - Roman Volkov; Didier Sinturele (Недвижимость: экономика, управление, 2021)
Corporate trajectories ultimately determine economic growth or recession. They depend on the choice of development strategies selected for corporate management systems designated for commercial real estate projects. Strategic focusing tools of corporate management systems are used to select the best corporate development strategies.